THE DILEMMA OF FULFILLING CHILDREN'S RIGHTS AMONG SMALL-SCALE PALM OIL FARMERS IN WEST KALIMANTAN - Pangeran Nasution (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Smallholder oil palm plantations have become a central pillar of rural livelihoods in many parts of Indonesia, including West Kalimantan. While governance and policy studies often frame oil palm expansion primarily in terms of production and economic growth, its social consequences—particularly for children within smallholder households—remain underexplored. This article examines the relationship between smallholder oil palm resilience, local governance practices, and the fulfillment of children’s rights through the lens of the anthropology of government. Drawing on qualitative ethnographic research conducted in Kapuas Hulu and Sintang Regencies, West Kalimantan, this study argues that oil palm functions not merely as an economic commodity but as a crop regime that structures daily rhythms, labor relations, and moral orientations within smallholder families. In this context, children frequently occupy adaptive positions within household survival strategies, including domestic labor and informal economic participation, which may undermine their rights to education, health, and well-being. The findings further demonstrate that children’s vulnerability in smallholder oil palm regions cannot be understood solely as a cultural or household-level issue. Rather, it is closely linked to fragmented local governance practices. The state emerges as a selective presence: strongly engaged in promoting productivity and economic stability in the oil palm sector, yet largely absent in integrating child protection mandates into economic and village governance policies. This selective engagement generates governance gaps that effectively delegate social risks to households and local communities. By positioning children as an analytical lens rather than merely as policy beneficiaries, this article contributes to government studies by highlighting how economic development policies shape everyday governance and reproduce social inequality at the household level. The study underscores the need for child-sensitive governance frameworks that integrate economic development with social protection in rural and agrarian contexts.